Síntese verde de nanopartículas de prata mediada por extratos vegetais de Astrocaryum aculeatum (Tucumã) - Tapudima, Marco Antônio Carvalho (Brasil, 2023)
Traditional methodologies for the synthesis of metallic nanoparticles can use toxic reagents that result in negative impacts on both the environment and human health. Thus, a safer alternative for the production of these nanomaterials is based on the concepts of Green Chemistry, where natural resources are used, such as the use of plant extracts for the synthesis of metallic nanoparticles. In this context, the present work investigated the green synthesis of AgNPs from plant extracts of tucumã pulp (Astrocaryum aculeatum). With the aid of molecular absorption electronic spectroscopy in the UV-Vis region, it was possible to investigate the influence of different reaction parameters on the stability and rate of formation of nanoparticles. The UV-Vis spectra of the reaction media indicated the temporal evolution of a band centered between 405-415 nm that is related to the phenomenon of surface plasmon resonance due to the formation of AgNPs. The electronic transitions associated with the phytochemicals present in the plant extract were located in regions of shorter wavelength (200-280 nm) and tended to reduce absorbance with the progress of the reaction. Such information indicates the participation of these biomolecules in the process of reduction of silver cations. The results also showed that the combination of high pH (9) and higher concentration of plant extract in the reaction medium produced a greater amount of AgNPs and more stable colloids. Also noteworthy is the great influence of acidity/basicity on the reaction of heterolytic scission of O-H bonds of biomolecules in the plant extract, species that act as reducing agents of silver cations, and for this reason, can modify the rate of formation of nanoparticles.